Tengka, identity politics, and the Fiqh of civilization: The authority of Madura’s Kiai in the post-truth era - Taufiq, Muhammad; Amalia Syahidah, Jihan; Fauzinudin Faiz, Muhammad; Erie Hariyanto, (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2024)
This paper explores the role of tengka, a distinctive moral ethic of Madurese culture, in addressing the escalating identity politics in the post-truth era. It focuses on how religious leaders, known as Kiai, in Pamekasan, Madura, respond to identity politics by applying the concept of Fiqh of civilization as a framework for analysis. The study uses a socio-legal approach to explore three key aspects of the Kiai's role: the shifting dynamics of identity politics among the Kiai, the integration of tengka into their approach to identity politics, and the potential benefits and obstacles in this integration process. The findings reveal that the identity politics of the Madura’s Kiai authorities have experienced substantial evolution in the post-truth era. Despite various challenges faced by tengka in the context of identity politics, it presents substantial opportunities for internalization as a strategy to tackle these issues. This aligns with the Fiqh of civilization, which formulates the anticipation of identity politics in realizing al-mashālih al-'ammah (public interest) and strengthening religious moderation. The academic contribution of this research lies in the Fiqh of civilization, which is the contextualization of Fiqh al-siyāsah in analyzing identity politics, offering a unique perspective on the interaction between traditional moral and ethical values and the challenges of modern society.